Analisis Kekuatan Fishing Tools Holder 50.000 lbs menggunakan Metode Finite Element - Widiantoro, Heri; Arifin, Devi Eka Septiyani; Setiawan, Dibyo; Pasya, Azdane Peprial Indika (Universitas Muria Kudus, 2023)
Finite element numerical simulation (FEA) has a function to analyze the design model and as a validation of the analysis results against manual calculations. FEA simulation uses specialized software to save time and cost. The purpose of the FEA simulation on this design model is to analyze the strength of the design model against a deformation. In this study, a strength test will be carried out on one of the sub-assemblies on the fishing equipment tensile and compressive testing machine, namely the fishing tools holder sub-assembly. The reason for the simulation is that the sub-assembly is directly related to compressive or tensile forces with relatively large units. The material used for this sub-assembly design is SS400 material or ASTM A36 Carbon Steel. The simulation process was carried out in 10 iterations using the curvature-based mesh method with mesh size settings of 10, 9, 8, 7, 6, 5.8, 5.6, 5.4, 5.2, and 5. The maximum stresses that occurred and reached convergence were at mesh sizes 5.8, 5.6, 5.4, and 5.2 in sequence with stress values of 137 MPa, 136 MPa, 142 MPa, and 135.7 MPa, respectively. The finite element analysis results show that the fishing tools holder design produces a maximum stress of 142 MPa at the converging area, with a factor of safety (FoS) of 1.8. Based on these simulations, the design of the fishing tools holder can be implemented on the Fishing Equipments Tensile Test and Press Test Machine.